Ressignificando a produção de textos na alfabetização: experiências com a retextualização digital - Silva, Natany Avelar (2019)
The research elects as theme the issue of the production of texts in the literacy. Although the written modality is recognized as a linguistic-discursive practice of substantial importance for the insertion of students in the literate universe, teaching the production of written texts in literacy still faces numerous challenges. The poor performance presented by the students has been evidenced by the evaluations (internal and external) and assumed relevance in the complaints made by the teachers. In this sense, the present dissertation aims to analyze the textual and discursive aspects used by literacy students in the process of retextualization of short stories. Thus, the question that guides the present work is: What textual and discursive aspects are relevant to the production of a retextualization in digital environment? This research assumes relevance in function of approaching the production of texts in a discursive perspective in which various aspects are considered beyond the study of the form (linguistic correction and formal presentation of the text), notably, observed in a traditional work with the production of texts. in school. In the proposal in question, the production conditions and the potentialities of the different semioses in the process of meaning construction deserve to be highlighted. For the basis of the studies was carried out a theoretical research about the production of texts in literacy, the processes of retextualization, the concepts and methodological referrals for a teaching of the production of texts from the perspective of multi-concepts. Along with the theoretical studies, a field research was conducted in a class of the first year of elementary school (early years), which sought to observe how technological resources can favor the process of retextualization of tales in literacy. The analysis of the data was based on an interpretative approach of the texts produced by the students, since evaluating the writing of children should not be limited to the verification of the domain of formal linguistic questions, but should consider the discursive dimensions that constitute the interactions between subjects in constitution, therefore, the methodology used was discursive analysis, which made possible the unitarization of two categories inherent to the research context: the appropriation of the linguistic system and the discursive textual organization. The results of this dissertation are limited in the context of a theoretical discussion about the production of texts in literacy, the importance of the resizing of the teaching of textual production in the perspective of multi- lessons and the role of the teacher in the direction of educational practices that favor the formation of students. authors. In addition, this work provides, as a product, an intervention project that contemplated the articulation between language practices (orality, reading, text production and linguistic-semiotic-discursive analysis), as well as a reflection on the use of technological resources in text production practices.